Hubungan Usia Dengan Kejadian Prolaps Uteri di Departemen Obstetri dan Ginekologi RSPAL dr. Ramelan surabaya - KETUT EDY SUDIARTA; MOCHAMAD ALVIRIO NEDYA RIZKA; MUHAMMAD RIZAL; NANDA ABIGAIL; RONALD PRATAMA (Universitas Hang Tuah, 2022)
ABSTRACT BACKGROUND: Uterine prolapse is the descent of the cervix, uterus, and both adnexa from their normal position into the vagina. In general, the incidence of pelvic organ prolapse is 41-50% in women aged over 40 years and will increase with increasing life expectancy, and uterine prolaps is the second most common after cystourethrocele. The incidence of uterine prolapse patients is not known with certainty. Some studies report the incidence of uterine prolapse in the elderly, but there are also studies that report mostly at the age of 20-35 years. Therefore, we conducted a study to determine the relationship between age and uterine prolapse. METHODS: The study used a cross-sectional approach to determine the relationship between age and uterine prolapse in the Obstetrics-Gynecology ward at the Naval Center Hospital Dr. Ramelan Surabaya for the period 2019 to 2021. The data is presented in the form of tables and statistical tests using Q2-Square. CONCLUSION: In the period 2019-2021, there were 1797 cases of gynecological patients in the gynecology inpatient room and 63 cases (3.5%) of them were uterine prolapse. The highest incidence was in the age group 60-64 years with 27.0% (n=17) with distribution based on the level of uterine prolapse the most were grade 3-4 with n = 69.8% (n=44) and grade 1-2 prolapse with 30.2% (n=19). The youngest age is 35 years old and the oldest is 79 years old. Treatment of 63 cases of uterine prolapse 38 cases (60.3%) underwent surgery and 19 cases (39,7%) 9.7%) Keyword: uterine prolapse, pelvic organ, pelvic surgery, management.